Modulation of regional carbon uptake by AMOC and alkalinity changes in the subpolar North Atlantic under a warming climate - Zhang, Qi; Ito, Takamitsu; Bracco, Annalisa (Frontiers in Marine Science, 2024)
The slowdown of the Atlantic Meridional Overturning Circulation (AMOC) and associated consequences on ocean carbon uptake could have large implications for the Earth's climate system and its global carbon cycle. This study analyzes ten Earth System Models from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and reveals that the regional carbon uptake in the subpolar North Atlantic under a high CO2 emission scenario moderately correlates with the decline in AMOC at 40°N. AMOC transports warm and salty subtropical waters to the subpolar regions. Models with stronger AMOC slowdown generally exhibit weaker surface warming and larger decline of surface salinity and alkalinity. We consider two plausible mechanisms linking the AMOC slowdown to the decline of regional CO2 uptake: the reduction in surface alkalinity and diminished subduction. The decline of surface salinity and alkalinity reduces the ocean's capacity to buffer acids leading to a reduced CO2 uptake. This important contribution is unique to the North Atlantic. Diminished convective mixing and subduction of surface water can further decrease the downward transport of anthropogenic carbon, as also shown in previous research. The centennial trends of pCO2 are decomposed into four components driven by temperature, salinity, alkalinity and dissolved inorganic carbon, revealing that alkalinity and dissolved inorganic carbon are both significant contributors. The alkalinity-driven pCO2 essentially follows surface salinity, establishing the linkage between AMOC slowdown and alkalinity decline. Our results indicate that alkalinity changes are important for the interplay between AMOC and the regional carbon sequestration ability across the late 20th and the entirety of the 21st century in the subpolar North Atlantic.